Group insurance as a form of bancassurance. Rights and protection of the insured - Ramírez Otero, Lorena Cecilia (2024)
A study is made of the regulation that considers a bancassurance operation to be one in which the financial company would enter into group insurance as a contracting party, which empowers it to market coverage among its customers, and determines how this provision implements a system of distribution of individual insurance. The work identifies the main effects on the consumer, which occur when the marketing financial institution exercises the role of contracting party; and by contrast, the advantages of regulating their roles and responsibilities as an agent and representative of the insurer, for the protection of policyholders and the centralized management of individual policies. This study is a review of the technical justification of this type of improper group insurance, in the context of the current regulatory developments of the intermediation activity.